2006
DOI: 10.1001/jama.295.13.joc60038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fondaparinux on Mortality and Reinfarction in Patients With Acute ST-Segment Elevation Myocardial Infarction: The OASIS-6 Randomized Trial

Abstract: ClinicalTrials.gov Identifier NCT00064428.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
0
10

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 762 publications
(70 citation statements)
references
References 13 publications
1
59
0
10
Order By: Relevance
“…Furthermore, the place of fondaparinux in the setting of PCI for patients with non-ST-segment-elevation acute coronary syndromes remains poorly defined. 16 The drug was found to be harmful in patients with ST-segment-elevation myocardial infarction 17 and current guidelines do not recommend its use in the setting of primary PCI (class III recommendation). 5 The use of glycoprotein IIb/IIIa inhibitors as bailout strategy (apparently included in the subgroup analysis of patients without planned use of these agents) may further distort the ability of ACT to predict especially ischemic complications because in general glycoprotein IIb/IIIa inhibitors are used as a bailout strategy in patients considered at imminent risk of complications (mostly ischemic complications).…”
Section: See Article By Ducrocq Et Almentioning
confidence: 99%
“…Furthermore, the place of fondaparinux in the setting of PCI for patients with non-ST-segment-elevation acute coronary syndromes remains poorly defined. 16 The drug was found to be harmful in patients with ST-segment-elevation myocardial infarction 17 and current guidelines do not recommend its use in the setting of primary PCI (class III recommendation). 5 The use of glycoprotein IIb/IIIa inhibitors as bailout strategy (apparently included in the subgroup analysis of patients without planned use of these agents) may further distort the ability of ACT to predict especially ischemic complications because in general glycoprotein IIb/IIIa inhibitors are used as a bailout strategy in patients considered at imminent risk of complications (mostly ischemic complications).…”
Section: See Article By Ducrocq Et Almentioning
confidence: 99%
“…Early in the course of ACS, the short-term use of parenteral anticoagulants, such as unfractionated heparin (UFH), low-molecular-weight heparin (LMWH), fondaparinux and bivaluridin, have reduced the incidence of thrombotic events [18,19,20,21,22,23,24]. A meta-analysis of randomized trials using UFH and ASA in patients with unstable angina pectoris showed a 33% reduction in myocardial infarction (MI) and cardiovascular mortality compared to placebo [20].…”
Section: Current Anticoagulation Therapymentioning
confidence: 99%
“…Free fatty acids are normally the primary fuel source for the heart but are toxic to the 17 myocardium in the ischemic setting causing sarcolemmal and mitochondrial membrane disruption [15]. evidence in favour of GIK (total 525 patients) [21,22], seven showed no difference (25,496 patients) [23][24][25][26][27][28][29], and 7 one showed increased harm (954 patients) [30].…”
mentioning
confidence: 99%
“…However, in 5 studies the rates were not mentioned at all 7 [28,26,27,29,21]. Some studies recorded symptomatic hypoglycaemia only (not biochemical) and this would 8 significantly underestimate true biochemical hypoglycemia [22,25].…”
mentioning
confidence: 99%
See 1 more Smart Citation